Perfect little monsters - He, Cindy R. X.; OverDrive, Inc. (Naperville, Illinois : Sourcebooks Fire, 2024)
The most popular--and hated--girl in school is murdered and the suspects are aplenty, but when Dawn becomes the number one, she must uncover the truth before another person dies.
Electronic book.
Ages 14-18.
Grades 10-12.
Electronic reproduction.
Keywords: Advantage title -- Fiction; Advantage title -- Fiction; Murder -- Fiction; High schools -- Fiction; Schools -- Fiction; Mystery and detective stories; Detective and mystery fiction; Novels; Electronic books; Detective fiction; Mystery fiction